2017
DOI: 10.1007/s10974-017-9468-6
|View full text |Cite
|
Sign up to set email alerts
|

Mouse soleus (slow) muscle shows greater intramyocellular lipid droplet accumulation than EDL (fast) muscle: fiber type-specific analysis

Abstract: Skeletal muscle is the main tissue of lipid metabolism and accordingly is critical for homeostasis and energy production; however, the determinants of lipid accumulation in skeletal muscle are unknown. Here, we examined whether the soleus muscle (predominantly slow-twitch fibers) has a higher lipid accumulation capacity than that of the extensor digitorum longus (EDL, predominantly fast-twitch fibers) muscle in mice. Soleus and EDL muscles were harvested from male C57BL/6J mice. The mRNA levels of genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…TAGs, an important energy source, are one of the markers of slow‐twitch fibers because IMCL droplets were more prevalent in the soleus than in EDL tissue (Figure 1, supporting information). Furthermore, Komiya et al have demonstrated that the TAG contents of Type IIa fibers were higher than those of Type I fibers . However, TAGs visualized with fluorescent probes include multiple molecular species.…”
Section: Discussionmentioning
confidence: 99%
“…TAGs, an important energy source, are one of the markers of slow‐twitch fibers because IMCL droplets were more prevalent in the soleus than in EDL tissue (Figure 1, supporting information). Furthermore, Komiya et al have demonstrated that the TAG contents of Type IIa fibers were higher than those of Type I fibers . However, TAGs visualized with fluorescent probes include multiple molecular species.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid droplets were stained with BODIPY 493/503 (Life Technologies) diluted in 10% (v/v) dimethyl sulfoxide in PBS to a concentration of 1 mg/mL [17]. Frozen cardiac tissue or NRCMs were fixed with 4% paraformaldehyde for 20 min and then immersed in BODIPY 493/503 solution for 30 min at 37 °C.…”
Section: Bodipy 493/503 Stainingmentioning
confidence: 99%
“…And EN occupied the largest number of specific PASs that uniquely expressed. Moreover, we performed a further comparative analysis of tissue-specific PASs between SM and EDL in 1 d and adult periods (366 and 278), which were often used as representative muscles dominated by slowtwitch (type I) and fast-twitch (type II) fibers in animal experiments [44]. Gene ontology analysis revealed that these genes containing tissue-specific PASs (p < 0.05) were mainly involved in oxidation-reduction process, cell division, response to drug, apoptotic process, and inflammatory response in terms of molecular function (Figure 4(b)).…”
Section: Tissue Specificity Analysis Of Passmentioning
confidence: 99%